2023
DOI: 10.1039/d3cc00836c
|View full text |Cite
|
Sign up to set email alerts
|

Construction of trifluoromethyl-containing heterocycles from trifluoroacetimidoyl chlorides and derivatives

Abstract: Recent advances in the direct synthesis of trifluoromethyl-containing heterocycles from trifluoroacetimidoyl chlorides (TFAICs) and derivatives, including trifluoroacetimidohydrazides (TFAIHs) and CF3-imidoyl sulfoxonium ylides (TFISYs), are systematically summarized and discussed. The cascade...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 86 publications
(76 reference statements)
0
5
0
Order By: Relevance
“…Moreover, it can substantially modify the lipid solubility and biological activities of the parent compounds. 24,25 Given these unique properties, the development of trifluoromethylation reagents and reactions has been a critical area of research in organic and medicinal chemistry for nearly five decades. 26,27 In 2014, the group of Cho reported a photocatalyzed hydro-trifluoromethylation of terminal alkynes 1 using trifluoromethyl iodide 2 as the trifluoromethylating reagent.…”
Section: Photocatalytic Cascade Reactions Via Multiple Set Processesmentioning
confidence: 99%
“…Moreover, it can substantially modify the lipid solubility and biological activities of the parent compounds. 24,25 Given these unique properties, the development of trifluoromethylation reagents and reactions has been a critical area of research in organic and medicinal chemistry for nearly five decades. 26,27 In 2014, the group of Cho reported a photocatalyzed hydro-trifluoromethylation of terminal alkynes 1 using trifluoromethyl iodide 2 as the trifluoromethylating reagent.…”
Section: Photocatalytic Cascade Reactions Via Multiple Set Processesmentioning
confidence: 99%
“…It is found that TFISYs could be applied as 1‐, 3‐ or 5‐atom synthons to build structurally diversified CF 3 ‐containing heterocycles. Inspired by the good applicability of highly reactive PDFA and our continuous effort on the efficient synthesis of trifluoromethyl‐substituted heterocycles, [ 15 ] we wish to merge TFISYs with PDFA to establish a more general and practical approach for the construction of 2‐trifluoromethyl quinolines. Herein, we report our recent findings about multi‐component reaction of TFISYs and amines with PDFA as a C1 synthon in the presence or absence of elemental sulfur under simple heating conditions (Scheme 1d).…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…Due to the high lipophilicity, metabolic stability, and binding selectivity of the trifluoromethyl group, the introduction of it onto the pyrrole skeleton greatly alters the physicochemical properties and promotes the applications (several examples in Figure ). At present, the strategies for the construction of CF 3 -pyrroles can be divided into two main categories including trifluoromethylation of pyrroles by trifluoromethyl reagents and cyclization of CF 3 -containing building blocks . Compared with the latter, direct trifluoromethylation often suffers from the puzzle of regioselectivity and requires preprepared pyrroles as the starting materials.…”
mentioning
confidence: 99%